2009
DOI: 10.1007/s11420-009-9107-x
|View full text |Cite
|
Sign up to set email alerts
|

SAS Weekly Rounds: Avascular Necrosis

Abstract: Osteonecrosis of the femoral head is a condition that affects upwards of 10,000 individuals in the USA each year. The peak incidence is in the fourth decade of life, and overall, there is a male preponderance. The condition accounts for up to 12% of total hip arthroplasties performed in developed countries. The etiology can be traumatic or non-traumatic, with 90% of atraumatic cases attributed to corticosteroid therapy or excess alcohol consumption. Osteonecrosis of the femoral head reflects the final common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 154 publications
1
13
0
Order By: Relevance
“…Despite the fact that there were insufficiencies in our technical scale (lake of magnetic resonance imaging and bone scintigraphy), aseptic osteonecrosis main location was the femoral head, and most of patients were rather young. Our results were close to those from Burkina Faso [7] and to data from western countries [14]. Men were more affected than women, as previously observed [15].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that there were insufficiencies in our technical scale (lake of magnetic resonance imaging and bone scintigraphy), aseptic osteonecrosis main location was the femoral head, and most of patients were rather young. Our results were close to those from Burkina Faso [7] and to data from western countries [14]. Men were more affected than women, as previously observed [15].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have demonstrated excellent outcomes with the use of improved cementing techniques and contemporary uncemented components. Seyler TM et al have compared around 23 studies between 1989 and 2004 and have found success rates varying from 52% to 98 % [50,51] . Ours is a prospective study comprising of 32 patients with 32 uncemented total hip arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
“…Results are generally positive with early recovery from disabilities (2)(3)(4). The intravenous administration is not free from complications (5,6). Frequently, an avascular necrosis of bones may occur due to several mechanisms not yet cleared (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The intravenous administration is not free from complications (5,6). Frequently, an avascular necrosis of bones may occur due to several mechanisms not yet cleared (5)(6)(7). Femoral heads represent a specific target as reported recently in adult patients even with a bilateral involvement (2,8).…”
Section: Introductionmentioning
confidence: 99%